Synthesis and biochemical characterization of quasi-stable trimer models of full-length amyloid β40 with a toxic conformation. Issue 2 (6th December 2018) - Irie, Yumi; Hanaki, Mizuho; Murakami, Kazuma; Imamoto, Tsuneo; Furuta, Takumi; Kawabata, Takeo; Kawase, Taiji; Hirose, Kenji; Monobe, Yoko; Akagi, Ken-ichi; Yanagita, Ryo C.; Irie, Kazuhiro
Abstract : The only trimer model to exhibit weak but significant neurotoxicity against SH-SY5Y cells was the one which was linked at position 38. Abstract : Here, we report the first synthesis of quasi-stable trimer models of full-length Aβ40 with a toxic conformation using a 1, 3, 5-phenyltris-l -alanyl linker at position 34, 36, or 38. The only trimer to exhibit weak neurotoxicity against SH-SY5Y cells was the one which was linked at position 38. This suggests that such a propeller-type trimer model is not prone to forming oligomers with potent neurotoxicity, which is in contrast with its corresponding dimer model.